Avaliação de habitações construídas com painéis de PVC preenchidos com concreto - Latosinski, Karina Trevisan (2015)
Brazil has a high deficit of housing. However, it is known that adequate housing condition may reflect in improvements in the quality of life of the population. Aiming the solution of this problem and the delivery of increased productivity and quality to residential buildings, new techniques and new materials are developed. This study has sought a better understanding of the innovative building system composed of polyvinyl chloride profiles - PVC - filled with concrete through assessments made during and after construction. Six housing complexes were visited in different cities of the state of Rio Grande do Sul, BR, where the questionnaires were administered to residents. The following housing complexes were examined: Canoas Minha Terra II, Valparaíso Condominium, São Luiz Condominum, Loteamento Park Novo Hamburgo, Residential Terra Nativa and Park São Pedro whose typology and constructive standards were diverse. In addition, the implementation of the Canoas Minha Terra I project was accompanied in order to identify the main construction stages of a building with such construction system and to take samples for testing. These samples showed inferior results when compared to the appropriate norms. The residents reviews were positive about the comfort and appearance of the building. However, the main problem reported and identified in loco was the excessive accumulation of moisture on the walls following condensation, and consequently the appearance of mold. This problem was less frequent in the condominium that had internal finishing of the rooms with no exposed PVC. Therefore, the constructive system at stake provides more rapidity, transportation facility and execution when compared to conventional methods. However, it requires projective artifices such as coating or increased ventilation, so that users do not have inconveniences generated by the accumulation of water on the walls.